Laughing it Out: Strategies of Affectively Remembering Dictatorship in Griselda Gambaro’s Antígona furiosa - Laufenberg, Marin (Latin American Theatre Review, 2018)
This study brings into focus the interaction between levels of watchers and the watched in Griselda Gambaro’s 1986 work, Antígona furiosa. Combinations of the laughable and the serious are shown to hold affective ways of understanding and remembering Argentina’s most recent military dictatorship (1976-1983). Belittling and making light of Antígona’s situation, Antinoo and Corifeo act as grotesque buffoons. The audience sometimes laughs with the buffoons, but then later reflects on it; at other moments, the two men mock and laugh while the audience merely observes their cruelty. Through both taking part in and observing nuances of humor, the importance of the witness’s role in the theatre and in society is heightened and the audience ultimately acquires a new way of knowing the trauma of the dictatorship.